Pengaruh Self-Efficacy dan Pemberian Reward Melalui Motivasi Terhadap Peningkatan Kinerja Agen: (Studi Kasus PT. Prudential Pruaini Cabang Medan) - Virdinia, Thasya; Rahma, Tri Inda Fadhila; Marliyah, Marliyah (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
In the competitive insurance industry, agent performance is a key factor in achieving company success. Various factors can affect an agent's performance, including motivation, self-efficacy, and the reward system implemented by the company. This study aims to analyze the influence of self-efficacy and reward on the performance of insurance agents of PT. Prudential Pruaini Medan Branch, with motivation as a mediation variable. Using a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, data was collected through a questionnaire distributed to 60 agents using a non-probability sampling method and analyzed using SmartPLS software. The results of the study show that self-efficacy has a significant influence on the motivation and performance of agents. Giving rewards has a positive effect on motivation, but does not have a direct effect on performance. Interestingly, motivation was shown to significantly mediate the relationship between self-efficacy and rewarding and agent performance. This study confirms that intrinsic factors (self-efficacy) and extrinsic (reward) factors contribute significantly in improving the motivation and performance of insurance agents. The practical implication of this research is the need to develop training programs to increase self-efficacy as well as performance-based reward systems to increase agent effectiveness.